Closure of oroantral fistula with rotational palatal flap technique - David B. Kamadjaja (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Oroantral fistula is one of the common complications following dentoalveolar surgeries in the maxilla. Closure of oroantral fistula should be done as early as possible to eliminate the risk of infection of the antrum. Palatal flap is one of the commonly used methods in the closure of oroantral fistula. A case is reported of a male patient who had two oroantral communication after having his two dental implants removed. Buccal flap was used to close the defects, but one of them remained open and resulted in oroantral fistula. Second correction was performed to close the defect using buccal fat pad, but the fistula still persisted. Finally, palatal rotational flap was used to close up the fistula. The result was good, as the defect was successfully closed and the donor site healed uneventfully.